Formation pathways of light hydrocarbons in deep sediments of the Danube deep-sea fan, Western Black Sea. (December 2020) - Pape, T.; Haeckel, M.; Riedel, M.; Kölling, M.; Schmidt, M.; Wallmann, K.; Bohrmann, G.
Abstract: We report on the geochemistry of light hydrocarbons and pore water in sediments down to 147 m below seafloor (mbsf), at two sites within the gas hydrate stability field of the Danube deep-sea fan, Black Sea. Sediments were drilled with MARUM-MeBo200 and comprise the transition from limnic to the recent marine stage. Stable C/N ratios (mean 5.1 and 5.6) and δ 13 C-Corg values (mean −25.8‰ V-PDB) suggest relatively uniform bulk organic matter compositions. In contrast, pore water δ 2 H and δ 18 O values varied considerably from approx. −120‰ to −30‰ V-SMOW and from −15‰ to −3‰ V-SMOW, respectively. These data pairs plot close to the 'Global Meteoric Water Line' and indicate paleo temperature variations. Depletions of pore water in 2 H and 18 O below 40 mbsf indicate low temperatures and likely reflect conditions during (the) last glacial period(s). Methane was much more abundant than the only other hydrocarbons found in notable concentrations, ethane and propane ((C1 /(C2 +C3 ) ≥20, 000). Relatively constant δ 13 C–CH4 (~−70‰ V-PDB) and δ 13 C–C2 H6 (~−52‰ V-PDB) values with depth indicate that methane and ethane are predominantly of microbial origin and that their formation was not limited by carbon availability. In contrast, δ 2 H–CH4 values varied in a large range (approx. −310 to −240‰ V-SMOW) with depth and positively correlated with trends observed for δ 2 H–H2 O. Isotope separations (Δδ 13 C(CH4 –CO2 ), Δδ 2 H(CH4 –H2 O)) substantiate that microbial carbonate reduction (CR) is the prevalent methanogenic pathway throughout the sediments irrespective of their geochemical history. Remarkably, in δ 13 C–CH4 – δ 2 H–CH4 diagrams widely used, samples characterized by δ 2 H–CH4 values more negative than approx. −250‰ plot out of the field assigned for pure CR. We conclude that assignments of microbial methanogenic pathways based on classical interpretations of δ 13 C–CH4 – δ 2 H–CH4 pairs can lead to misinterpretations, as severe 2 H-depletions of methane formed through microbial CR can result from 2 H-depletions of the pore water generated during low-temperature climatic periods. Highlights: MeBo drilling in Danube fan down to 147 m recovered limnic to marine deposits. Molecular and stable isotope characterization of light hydrocarbons, CO2, and H2 O. H and O isotopic compositions of pore water reflect paleoclimate variations. Isotope relations prove microbial carbonate reduction as major methanogenic pathway. Control of δ 2 H–CH4 by δ 2 H–H2 O may lead to misinterpretation of methanogenic paths.